فرموداتِ اقبال اور تحریکِ پاکستان : ایک توضیحی مطالعہ: Iqbal’s sayings and the movement of Pakistan: An explanatory study - محمد شکیل بھنڈر; ڈاکٹر محمد رمضان (Tashkeel e Jadeed, 2025)
Allama Iqbal played a key role in the freedom movement. He used not only his poetry but also his writings, speeches and letters to get the Muslims of the Indian subcontinent free from the British and save them from the slavery of the Hindus. In this regard, you gave a historic sermon on 29th December 1930 in Allahabad. In which you presented the two-nation theory. In it, you mentioned two big nations, Hindus and Muslims, apart from small nations. You demanded a separate homeland due to the large proportion of Muslim population in Punjab, Sarhad, Sindh and Balochistan. In addition to his poetry, he also mentioned these provinces in his speeches, writings and letters, which proved to be a milestone in the achievement of independence and the establishment of Pakistan.